O sonho coletivo da casa própria: a articulação da economia solidária com a educação popular no cooperativismo habitacional autogestionário - Dickmann, Ivanio (2018)
This dissertation analyzes self-managed housing cooperativism and its connections with popular education and solidarity economy. It rescues the history of cooperativism as an instrument of struggle of workers who organized to overcome the oppression of factories and tells how this movement has consolidated over the years and has pluralized in various branches spreading throughout the world. It analyzes the cooptation of cooperativism by capital and its ideological distortion, as well as its re-signification and its new manifestation in the solidarity economy movement, retaking the principles of the pioneers of the first english cooperatives. It presents popular education as the pedagogical element of this new cooperativism that has the task of making people who participate in cooperatives understand that they can contribute to the self-management of all cooperative processes. Popular education has the function of consolidating the political and economic significance of the movement, as well as contributing to the construction of a new cooperative, fair and supportive culture. These historical findings, theoretical and practical, are put to the test in the day-to-day of brazilian housing cooperatives that transit through all possible models and types. We analyze and list these different forms of creation and management of housing cooperatives, making an effort to organize them by the form of management (self-management and exo-management), their economic sustainability (self-sustaining and self-financed), and the institutional life cycle (open and closed). Then we made a list of the types of cooperatives that suffer from historical distortion (drawer cooperatives, façade cooperatives and belly for rent cooperatives) and housing cooperatives that are models tuned in and committed to the struggle for working-class housing (labor movement cooperatives, cooperatives of the housing movements and cooperatives of the solidarity economy movement). We illustrate how this whole framework is in connection with the Central Housing Cooperative of Brazil-COOHABRAS, with which we face all the challenges of the popular organization in search of a home